Bacterial and Archaeal Specific-Predation in the North Atlantic Basin - Seyler, Lauren M.; Tuorto, Steve; McGuinness, Lora R.; Gong, Donglai; Kerkhof, Lee J. (Frontiers in Marine Science, 2019)
Stable isotope probing (SIP) was used to track prokaryotic and eukaryotic carbon uptake along a meridional transect (Long. 52˚W) in the North Atlantic to assess if 13C-resource partitioning between bacteria and archaea and 13C-labeled eukaryotic predators could be detected. One-liter SIP microcosms were amended with 13C-acetate or 13C-urea and incubated for 48 hours. Our data indicated archaea often outcompeted bacteria for 13C-urea while both archaea and bacteria could incorporate 13C-acetate. This 13C label could also be tracked into eukaryotic microbes. The largest number of 13C-labeled eukaryotic OTUs, and the greatest percentage of eukaryotic 13C signal, were observed in conjunction with both archaeal and bacterial 13C incorporation, suggesting that most eukaryotic predators do not distinguish between archaeal and bacterial prey. However, other 13C-eukaryotic OTUs were exclusively associated with either 13C-archaeal or 13C-bacterial OTUs. These archaeal-specific and bacterial-specific 13C-eukaryotic OTUs were related to known bactivorous predators including Ancyromonas, Amastigomonas, Cafeteria, and Caecitellus. Our SIP findings suggest both resource partitioning between bacteria and TACK (Thaumarchaeota, Aigarchaeota, Crenarchaeota, and Korearechaeota) archaea and selective predation by eukaryotic predators. Determining the equalizing mechanisms for co-existence in the marine environment can help map predator/prey interactions to better estimate carbon flow in the deep ocean.